Molecular characterisation and functional analyses of Musa acuminata Pathogenesis-related 10 (MaPR10) gene / Arullthevan Rajendram - Arullthevan , Rajendram (2022)
Plant immunity to pathogen infections is a dynamic response that involves multiple organelles and defence signalling systems such as induced systemic resistance (ISR) and systemic acquired resistance (SAR). The latter is mediated by pathogenesis-related proteins (PR), a common type of plant protein known for its diverse role in plant innate immunity. In this study, two novel PR protein variants were isolated from two Musa acuminata cultivars namely Berangan and Grand Naine (ITC 1256). Sequence characterisation study carried out on 69 genomic and transcript clones of M. acuminata PR (MaPR) gene revealed that the PR1-like gene that was reported to involve in Meloidogyne incognita - Grand Naine (ITC 1256) interaction in Al-Idrus et al. (2017) actually belongs to PR10 gene group despite showing 81–95 % similarity with M. acuminata PR1 sequences in the GenBank and Banana Genome Hub database. This discrepancy was further discussed and linked to miss-curation of the previous sequence data entered in the two sequence databases, hence the isolated clones were denoted as MaPR10 instead. Phylogenetic analysis revealed that the deduced amino acid sequences from 69 genomic and transcript clones of MaPR10 clustered into four distinct groups, while 44 genomic clones clustered into three distinct groups. Southern blot result corroborated that of found in phylogenetic analysis confirming that MaPR10 gene was present in at least three copies in both Berangan and Grand Naine genomes studied. Two sequence variants i.e., MaPR10-BeB5 and MaPR10-GNA5, were chosen for a subcellular localisation study in onion epidermal cells. Meeting the expectation of the in silico prediction, this study confirmed that the two protein variants were localised intracellularly. In addition, functional analyses confirmed that both protein variants function as β-1,3-glucanases and ribonucleases. While the former is novel, the latter is a common function of the members of PR10 gene family in plants. When tested on three economically important fungal species Aspergillus fumigatus, Aspergillus niger, and Fusarium oxysporum f. sp. cubense: Tropical Race 4, both protein variants only significantly (p < 0.05) inhibited the growth of A. fumigatus. This study reports MaPR10 protein variants as the first plant protein to exhibit antagonistic effect towards A. fumigatus and the first member of PR10 protein family to exhibit β-1,3-glucanase function.